STRATEGIC MAINTENANCE AND TECHNOLOGICAL INNOVATION AS RESPONSES TO STRUCTURAL CHALLENGES IN RENEWABLE ENERGY PRODUCTION CHAINS - Feitosa Neto, Alcides; Almeida, Antonio Werbiton Marinho; Florêncio, Francisco Fabio Braga; Santana, Givanildo Ximenes; Fontes, Irene Mendes; de Souza, José Reudson; Barbosa, Márcio Carneiro; Bastos, Moésio da Costa; Gomes, Rickardo Léo Ramos; Caracas Neto, Roberto Augusto; Dantas, Tovyska Braga; da Silva, William Neves (Seven Editora, 2026)
Renewable energy production chains play a central role in the global energy transition, as they are essential for reducing greenhouse gas emissions and promoting a more sustainable energy matrix. However, the expansion and consolidation of these chains have revealed a set of structural challenges related to asset reliability, operational complexity, and the long-term sustainability of energy infrastructures. In this context, strategic maintenance and technological innovation emerge as critical elements for ensuring the resilience, efficiency, and competitiveness of renewable energy systems. A qualitative approach was adopted, as it is suitable for exploring phenomena that require a deeper understanding of contexts, processes, and interactions. Regarding methodological procedures, the research was classified as bibliographic. This type of procedure is based on the careful analysis of previously published scientific works, which constitutes one of the foundations of scientific knowledge construction. The general objective of this study is to analyze how strategic maintenance and technological innovation can function as effective responses to the structural challenges of renewable energy production chains, contributing to increased operational reliability, asset sustainability, and competitiveness within the energy sector. According to the study, maintenance management, when effectively integrated with new technologies and a comprehensive view of the production chain, represents a key factor in increasing operational reliability. Furthermore, efficient management enables more conscious use of resources and contributes to strengthening the sustainability of assets linked to electric energy generation. The relationship between maintenance management and the implementation of technological solutions proves to be highly beneficial for the energy sector, resulting in stronger and more effective performance.